PENGARUH LATAR BELAKANG PENDIDIKAN CHIEF FINANCIAL OFFICER, FINANCIAL DISTRESS, AUDIT TENURE TERHADAP AUDIT REPORT LAG - Entis Haryadi; Santi Octaviani; Sallyna Regita (Jurnal Akuntansi Manajemen (JAKMEN), 2026)
This study aims to obtain empirical evidence regarding the effects of the Chief Financial Officers (CFO) Educational Background, Financial Distress, and Audit Tenure on Audit Report Lag in property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative method using secondary data obtained through documentation techniques, specifically financial statements and annual reports published on the official website of the Indonesia Stock Exchange and the official websites of the respective companies. The sampling technique used was purposive sampling, resulting in a sample of 24 companies with a total of 62 observations after outliers were removed. The research data were analyzed using multiple linear regression. The results indicate that the Chief Financial Officers (CFO) Educational Background and Audit Tenure do not affect Audit Report Lag, whereas Financial Distress does affect Audit Report Lag.